AN OVERVIEW OF THE THYROHYOID MUSCLE, ITS CLINICAL AND SURGICAL IMPLIlCATIONS - Ramalingam, Sudha; Somanath, Deepa (Journal of Morphological Sciences; Vol 2 No 2 (2019): JMS, 2019)
Abstract: The thyrohyoid muscle is one of the infrahyoid muscles located on the deeper layer of the infrahyoid muscles attached to the oblique line of the thyroid cartilage. The activity of the THM is required in deglutition, phonation and respiration. This article explains the various aspects of the muscle regarding its anatomy, development and clinical correlation.